Using task-based activities for the first-year non-major students of English in speaking lessons at National Economics University = Sử dụng các hoạt động giao nhiệm vụ cho sinh viên không chuyên tiếng Anh trong các tiết học nói tại trường Đại học Kinh tế - Chu, Thị Kim Ngân (ĐHNN, 2017)
35 p.+ CD-ROM